PENGARUH SOCIAL MEDIA MARKETING CONTENT INSTAGRAM @KEDAIKOPIKULO TERHADAP SIKAP KONSUMEN - Praditha Ramadhanty; Ruth Mei Ulina Malau (Ilmu Komunikasi, FISIP Universitas Pasundan, 2020)
ABSTRACT Internet helps the public to access information anytime and anywhere. Likewise, with the trend in marketing, the presence of the internet makes digital media such as social media used as new media in marketing. Through social media, business people attract consumers’ attention, especially on the content provided. Marketing content on social media is one of the things that can make consumers more aware of the presence of a brand of goods or services. Because the content displayed through social media is a strong attraction for consumers and creates emotion for the audience. These emotions, that ultimately create a relationship between consumers and brands and generate the potential to make purchases that lead to consumer attitudes consisting of affective (emotion), cognitive (perception) and behavioural (action). This study aims to see how consumer attitudes can be affected by the content that is served through Instagram social media marketing content with the object is @kedaikopikulo. Data collection techniques in this study were the distribution of questionnaires to 100 respondents @kedaikopikulo and the method used was quantitative research methods. Based on the results of the study, there was an influence of 64.4% of social media content marketing Instagram on consumer behaviour with a correlation of 1,070 between the two variables which showed that there was a strong relationship between the two variables.